Development of innovative hybrid and intrinsically magnetic nanobeads as a drug delivery system. (August 2016) - Campodoni, Elisabetta; Adamiano, Alessio; Dozio, Samuele M; Panseri, Silvia; Montesi, Monica; Sprio, Simone; Tampieri, Anna; Sandri, Monica
Aim: Synthesis of superparamagnetic hybrid nanobeads (MHNs) made of iron-substituted hydroxyapatite nanophase mineralizing a self-assembling alginate (Alg) matrix to be used as drug carriers, with ability of remote activation by magnetic signaling.Materials & methods: Iron-doped apatite was heterogeneously nucleated on the self-assembling Alg matrix by a bioinspired mineralization process and MHNs are formed by a subsequent emulsification by oil-in-water technique.Results: The obtained MHNs exhibited biomimetic composition, adequate swelling properties in physiological-like environment and superparamagnetic properties. The assembling of Alg induced the egg-like rearrangement of the mineralized composite that was then stabilized through cross-linking reaction with calcium ions.Conclusion: The new MHNs can be considered as a promising biocompatible and bio-resorbable drug delivery system with magnetic properties, thus opening to smart applications in nanomedicine.